(untitled) (Zaporizhzhia Historical Review, 2021)
The primary aim of the article is to analyse the diplomatic relations between UNR (Ukrainska Narodna Respublika) and Belgium and the Netherlands in the period of 1919-1921. The author makes an attempt to study the process of negotiations between the governments of these two countries and find out the reasons that led to official non-recognition of Ukraine by those two countries.